L’impossible reproduction d’un collectif savant - Jean-Baptiste Devaux (Revue d’Histoire des Sciences Humaines)
This article aims at explaining the way economists identified as industrial economists tried to build an intellectual collective in order to impose their own definition of industrial organization in the field of economics. The paper deals with the history of this group, which as also been called “French industrial organization school”, from its frist years (at the middle of the 70’) until the beginning of the 90’. At this time, this group appeared as unable to reproduce and imposing its own jurisdiction of industrial organization. This work aims at describing social mechanisms which produced this impossible reproduction, exploring the way French economists tried to build a community but also the way social positions of its actors in the field of economics have been a drag for its success and expansion.